Epidemiologic trends and geographic distribution of patients with gallbladder and extrahepatic biliary tract cancers in Canada. Issue 10 (October 2021) - Xiao, Yasi; Cattelan, Leila; Lagacé, Francois; Ghazawi, Feras M.; Alakel, Akram; Grose, Elysia; Le, Michelle; Nechaev, Vladimir; Sasseville, Denis; Waschke, Kevin; Litvinov, Ivan V.
Abstract: Background: Gallbladder and biliary tract cancers are rare malignancies that carry a poor prognosis. Research on their epidemiologic trends is scarce. Methods: We performed a retrospective analysis of the data in Canada using population-based cancer registries from 1992 to 2010. The incidence and mortality of gallbladder and extrahepatic bile duct cancers were examined at the levels of provinces/territories, cities, and Forward Sortation Area (FSA) postal codes. Results: The incidence and mortality rates decreased over the study period. The average national incidence rate of gallbladder and biliary tract cancers was 30.92 cases per million individuals per year. Higher than average incidence rates were observed in Manitoba, Saskatchewan and Québec; there were contiguous regions with high incidence in Saskatchewan and Manitoba that suggest an area of putative case clustering. Higher incidence of gallbladder cancer was observed in women, whereas higher incidence of extrahepatic bile duct cancers was noted in men. Lower socioeconomic status and Hispanic race were found to be risk factors for gallbladder and biliary tract cancers. Conclusion: This is the first study to analyze the burden of gallbladder and biliary tract cancers in Canada. The geographic clustering trends present new avenues for research on environmental triggers.